Isopropyl 2,5-anhydro-3,4-di-O-tert-butyldiphenyl-silyl-L-ribonate - Glawar, A. F. G.; Watkin, D. J.; Sanjayan, G. J.; Tranter, G. E.; Edwards, Alison A.; Fleet, George W. J. (Acta Crystallographica Section E - Structure Reports Online, 2005)
Determination of the crystal structure of the title compound, C40H50O5Si2, firmly established its relative configuration and hence that of some related tetrahydrofuran carboxylates. The material crystallizes with Z' = 2. Except for the chiral centres, the two independent molecules are related by a pseudo-centre of symmetry.